Apical but not basal RV strain reflects right ventricular dysfunction in patients with dilated cardiomyopathy - Asmaa Ahmed Ali; Safaa Abo Alfadl Mohammed; Amal Mohamed Hamdy (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background RV dysfunction is an important predictor of morbidity and mortality in cardiac patients, especially those having dilated cardiomyopathy (DCM). Deformation imaging parameters (strain and strain rate) are established as new echocardiographic measures that allow for both global and regional RV function assessment. Previous studies showed that heterogeneous segmental deformation affects global RV function differently in various disease states. Echo-Doppler parameters of RV and LV function including RV global longitudinal strain, basal & apical RV strain, LV ejection fraction and LV global longitudinal strain were evaluated in 42 DCM patients & 28 normal subjects, aiming to assess the value of apical versus basal RV strain in detection of RV dysfunction in patients with dilated cardiomyopathy. Results DCM patients had significantly lower values of both RV global longitudinal strain and apical RV strain compared to normal subjects (p < 0.001). Basal RV strain did not significantly differ in DCM from normal. The apical RV strain correlated significantly with RV global longitudinal strain, LV ejection fraction and LV global longitudinal strain (p < 0.001 for all). Using ROC curve, a cut-off value of apical RV strain ≤ 29.5 distinguished RV dysfunction from normal with 91.2% sensitivity & 100% specificity. Conclusions RV apical but not basal strain reflects the status of RV function, and it represents a valuable measure to diagnose RV dysfunction in patients with DCM.